2015
DOI: 10.1111/1759-7714.12140
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte‐colony stimulating factor (GCSF) producing malignant pleural mesothelioma: Report of a case

Abstract: This report presents a case of malignant pleural mesothelioma (MPM) producing granulocyte colony-stimulating factor (G-CSF) that was treated by tumor resection. A 76-year-old male presented with a huge right-side chest wall tumor, along with a slight fever and chest wall pain. Laboratory findings showed an increased white blood cell count (64600 cells/μL) and C-reactive protein level (20.57 mg/dL). The patient underwent surgical removal of the tumor along with tissue from the chest wall and histopathological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In MPM, the two populations of MDSCs can be found in the TME; the granulocytic like subtype expressing CD15 high /CD33 low and the monocytic like subtype expressing CD15 low /CD33 high ( 15 , 67 , 75 , 76 ). Gr-MDSCs are recruited to the tumor site through G-CSF and GM-CSF released by MPM tumor cells and further differentiate into an immunosuppressive phenotype within the tumor ( 75 , 77 , 78 ). In MPM, MDSCs inhibit proliferation of CD8 + T cells through secretion of immunosuppressive molecules like reactive oxygen species (ROS), nitric oxide (NO) and kynurenine ( 75 , 79 , 80 ).…”
Section: Inflammatory Tumor Microenvironmentmentioning
confidence: 99%
“…In MPM, the two populations of MDSCs can be found in the TME; the granulocytic like subtype expressing CD15 high /CD33 low and the monocytic like subtype expressing CD15 low /CD33 high ( 15 , 67 , 75 , 76 ). Gr-MDSCs are recruited to the tumor site through G-CSF and GM-CSF released by MPM tumor cells and further differentiate into an immunosuppressive phenotype within the tumor ( 75 , 77 , 78 ). In MPM, MDSCs inhibit proliferation of CD8 + T cells through secretion of immunosuppressive molecules like reactive oxygen species (ROS), nitric oxide (NO) and kynurenine ( 75 , 79 , 80 ).…”
Section: Inflammatory Tumor Microenvironmentmentioning
confidence: 99%
“…We identified that meostheliomas can also release G-CSF, a second well-established cytokine that induces granulocyte infiltration. Notably, G-CSF production by mesothelioma is reported to confer a more aggressive phenotype (3941). Although we confirmed mesothelioma tumors release IL8 and G-CSF or prostaglandins, these factors had no impact in generating suppressive granulocytes.…”
Section: Discussionmentioning
confidence: 99%